2006
DOI: 10.1523/jneurosci.0666-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Functional Alteration in Adolescents Characterized by Early Childhood Behavioral Inhibition

Abstract: The temperamental style of behavioral inhibition has been characterized by exaggerated behavioral and neural responses to cues signaling threat. Virtually no work, however, has addressed whether behavioral inhibition may also confer heightened brain activation in response to positively valenced incentives. We used event-related functional MRI (fMRI) and a monetary incentive delay task to examine whether the neural response to incentives is also greater in adolescents characterized as behaviorally inhibited ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
236
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(269 citation statements)
references
References 58 publications
24
236
7
Order By: Relevance
“…According to significance of the amygdala in the startle reflex, this data indicates a potential role of amygdala-based circuits (and hypothetic significance of the bed nucleus of the striaterminalis) in familial risk for anxiety. This report is consistent with a study of increased stratial function to reward in adolescents with temperamental anxiety (Guyer et al, 2006). The meta-analysis of functional magnetic resonance and positron emission tomography studies of post-traumatic stress disorder, social anxiety disorder, and specific phobia in adults showed that all three disorders displayed hyperactivity in amygdala and insula (Etkin & Wager, 2007).…”
Section: Neuroimaging Results In Separation Anxiety Disorder In Childrensupporting
confidence: 90%
“…According to significance of the amygdala in the startle reflex, this data indicates a potential role of amygdala-based circuits (and hypothetic significance of the bed nucleus of the striaterminalis) in familial risk for anxiety. This report is consistent with a study of increased stratial function to reward in adolescents with temperamental anxiety (Guyer et al, 2006). The meta-analysis of functional magnetic resonance and positron emission tomography studies of post-traumatic stress disorder, social anxiety disorder, and specific phobia in adults showed that all three disorders displayed hyperactivity in amygdala and insula (Etkin & Wager, 2007).…”
Section: Neuroimaging Results In Separation Anxiety Disorder In Childrensupporting
confidence: 90%
“…The lack of distinction between uncertain-gain and uncertain-loss trials is less consistent with previous findings. Several studies using the MID task (e.g., Bjork et al, 2004;Guyer et al, 2006;Knutson et al, 2001;Knutson et al, 2003; have found greater NAcc activation for uncertain gain than loss (but not all; Juckel et al, 2006). The current paradigm used smaller incentives ($3.00 vs. $5.00), which might be too small to elicit this difference.…”
Section: Discussionmentioning
confidence: 79%
“…For such stimuli, the striatum represents a key subcortical structure that interacts with the PFC to support more automatic modes of processing. Guyer et al (2006) found that adolescents with a history of childhood BI showed greater striatal sensitivity to incentives, relative to adolescents without a history of childhood BI. Perez-Edgar et al (2014) suggested that this enhanced sensitivity specifically occurs in the subset of children with BI who possess a particular dopamine-related genotype.…”
Section: Reward Processing In Bimentioning
confidence: 95%
“…This includes motor response patterns, markers of activity in the autonomic nervous system (ie, heart rate and vagal tone; Kagan et al, 1987), cortical activity patterns (Calkins et al, 1996;McManis et al, 2002), and neuroendocrine profiles (ie, cortisol; Kagan et al, 1988;Schmidt et al, 1997). Recent advances in neuroscience have allowed this original amygdala-based model to be expanded to include broader perturbations in a distributed neural circuit, encompassing components of the PFC and striatum (Bar-Haim et al, 2009;Bishop et al, 2004;Guyer et al, 2006;Hardee et al, 2013;Helfinstein et al, 2012). Common across these diverse models is an emphasis on the relations between BI and hypersensitivity in neural circuitry rapidly engaged by automatic modes of processing and a resulting behavioral sensitivity to motivationally salient cues.…”
Section: Attention Orienting In Bimentioning
confidence: 99%